Serotonin 2B receptor slows disease progression and prevents degeneration of spinal cord mononuclear phagocytes in amyotrophic lateral sclerosis - Lawson, Roland (My University, 2016)
Microglia are the resident mononuclear phagocytes of the central nervous system and have been implicated in the pathogenesis of neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS). During neurodegeneration, microglial activation is accompanied by infiltration of circulating monocytes, leading to production of multiple inflammatory mediators in the spinal cord. Degenerative alterations in mononuclear phagocytes are commonly observed during neurodegenerative diseases, yet little is known concerning the mechanisms leading to their degeneration, or the consequences on disease progression. Here we observed that the serotonin 2B receptor (5-HT2B), a serotonin receptor expressed in microglia, is upregulated in the spinal cord of three different transgenic mouse models of ALS. In mutant SOD1 mice, this upregulation was restricted to cells positive for CD11b, a marker of mononuclear phagocytes. Ablation of 5-HT2B receptor in transgenic ALS mice expressing mutant SOD1 resulted in increased degeneration of mononuclear phagocytes, as evidenced by fragmentation of Iba1-positive cellular processes. This was accompanied by decreased expression of key neuroinflammatory genes but also loss of expression of homeostatic microglial genes. Importantly, the dramatic effect of 5-HT2B receptor ablation on mononuclear phagocytes was associated with acceleration of disease progression. To determine the translational relevance of these results, we studied polymorphisms in the human HTR2B gene, which encodes the 5-HT2B receptor, in a large cohort of ALS patients. In this cohort, the C allele of SNP rs10199752 in HTR2B was associated with longer survival. Moreover, patients carrying one copy of the C allele of SNP rs10199752 showed increased 5-HT2B mRNA in spinal cord and displayed less pronounced degeneration of Iba1 positive cells than patients carrying two copies of the more common A allele. Thus, the 5-HT2B receptor limits degeneration of spinal cord mononuclear phagocytes, most likely microglia, and slows disease progression in ALS. Targeting this receptor might be therapeutically useful.
Keywords: serotonin; 5-HT2B receptors; amyotrophic lateral sclerosis